El sistema de producción y comercialización y su incidencia en el volumen de ventas de la empresa de calzado “elegante”, cantón Guano, parroquia la matriz en el año 2015. - Silva Paredes, Tania Yesenia (2018)
This research is about “The production and marketing system and its impact on the sales volume of the ELEGANTE shoe, enterprise of Guano canton, the Matriz parish in 2015" The study is built by three chapters, those are explained as follows: First Chapter: It is constituted by the referential framework, in which there is the problem statement, formulation of the problem, specifics and general objectives, and the justification. Second Chapter: Consists of the theoretical framework, which contains background and the theoretical foundation, together the first unit that covers the generalities of the company, second unit refers to the production system, and finally the third unit regarding the marketing system and turnover. Third Chapter: The methods used for this research, the type of research used, the processing of information, the analysis and interpretation of results are detailed. Fourth Chapter: It is constituted by the conclusions and recommendations of the study, finally it will be possible to demonstrate the results to the problems raised at the beginning of the research.